Echocardiographic Screening for Detection of Congenital Heart Defect in Anorectal Malformation - Talukder, Md. Shah Alam; Al Mahmud, Md. Abdullah; Khan, Nadiuzzaman; Bari, M Saiful; Das, Shankar Chandra; Bari, Md. Shafiqul (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 184-187 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15356